Host range expansion of native insects to exotic trees increases with area of introduction and the presence of congeneric native trees. Issue 1 (21st November 2014) - Branco, Manuela; Brockerhoff, Eckehard G.; Castagneyrol, Bastien; Orazio, Christophe; Jactel, Hervé; Saura, Santiago
Summary Exotic tree species are widely used in forest plantations for their often high productivity and performance compared to native trees. However, these advantages may be compromised by herbivore damage. A list of European insect species that have expanded their host range to one of 28 exotic tree species introduced to Europe was compiled from a systematic literature review. The number of successful expansions was analysed using three predictors: (i) phylogenetic relatedness between exotic and European tree species; (ii) area covered by exotic tree species in Europe; and (iii) time since their introduction into Europe. In total, 590 host expansions of native insects to exotic trees were found, mainly of polyphagous species (43%); 25% of the cases reported some type of damage. Bark and wood borers, and defoliators were the dominant guilds. The number of recruited native insect species and cases where major damage occurred was positively correlated with the geographical extent of exotic trees in Europe and the presence of congeneric native trees. Synthesis and applications. The use of exotic tree species creates opportunities for native insect herbivores to expand their host range and increase their damage if they are widely planted next to native congeners. Risk assessment studies are recommended when introducing new tree species for forestry plantations. Risk assessments should include trials on susceptibility to any potential damaging organisms in the introduced range.